DEVELOPING INSTRUCTIONAL MEDIA OF ARABIC VOCABULARY USING QUIZIZ APPLICATION FOR STUDENTS OF GRADE X AT MAN 1 PAYAKUMBUH / ØªØ·ÙˆÙŠØ± ÙˆØ³ÙŠÙ„Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø¨Ø¨Ø±Ù†Ø§Ù…Ø¬ Ù‚ÙˆÙŠØ²ÙŠØ² Ù„ØªÙ„Ø§Ù…ÙŠØ° Ø§Ù„ØµÙ Ø§Ù„Ø¹Ø§Ø´Ø± ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Û± Ø¨Ø§ÙŠØ§ÙƒÙˆÙ…Ø¨ÙˆÙ‡ - Uci Fajar Riska; Devy Aisyah (Lughawiyah: Journal of Arabic Education and Linguistics, 2022)
This study aims to develop valid instructional media of Arabic vocabulary using Quiziz application for the X grade students at MAN 1 Payakumbuh. This research was Research and Development with three stages; define, design, and develop. The instruments to collect the data were questionnaire and validation sheet. Three validators involved in this research including instructional media, materials, and Arabic language experts. Data were analyzed using descriptive statistics. Results showed that instructional media of Arabic vocabulary that was developed using Quiziz application was highly valid. Score from each expert was 3.5, 3.8, and 3.1, and the mean score was 3.4 that was categorized highly valid. Thus, it can be concluded that the developed instructional media can be used by students of Islamic senior high school to learn Arabic vocabulary.